2021
DOI: 10.3390/nu13113817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sarcopenic Obesity and Its Confounders on Knee Range of Motion Outcome after Total Knee Replacement in Older Adults with Knee Osteoarthritis: A Retrospective Study

Abstract: Sarcopenic obesity is closely associated with knee osteoarthritis (KOA) and has high risk of total knee replacement (TKR). In addition, poor nutrition status may lead to sarcopenia and physical frailty in KOA and is negatively associated with surgery outcome after TKR. This study investigated the effects of sarcopenic obesity and its confounding factors on recovery in range of motion (ROM) after total knee replacement (TKR) in older adults with KOA. A total of 587 older adults, aged ≥60 years, who had a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Obese patients have larger lower limb loads and less rehabilitation training, thus leading to poor knee function recovery. Previous study has shown that BMI levels are negatively associated with lower limb muscle strength and muscle mass, and that obese people with reduced muscle mass are prone to limited activity, all of which limit the recovery of knee function (16). Hyperglycemia leads to the reduction of blood vessels at the incision, the decrease of phagocyte number and phagocytic capacity, the decrease of leukocyte chemotaxis and protein synthesis ability, the decrease of immune responses, and limits the formation of fibroblasts and collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Obese patients have larger lower limb loads and less rehabilitation training, thus leading to poor knee function recovery. Previous study has shown that BMI levels are negatively associated with lower limb muscle strength and muscle mass, and that obese people with reduced muscle mass are prone to limited activity, all of which limit the recovery of knee function (16). Hyperglycemia leads to the reduction of blood vessels at the incision, the decrease of phagocyte number and phagocytic capacity, the decrease of leukocyte chemotaxis and protein synthesis ability, the decrease of immune responses, and limits the formation of fibroblasts and collagen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, symptoms and physical impairments that are related to lower limb OA involving joint pain and stiffness, muscle weakness, and reduced sensory function can be deleterious to balance performance and contribute to the probability of falling. Moreover, changes in joint structure, such as osteophyte formation and cartilage degeneration, may alter mobility patterns, which may in turn negatively impact balance [ 62 , 63 , 64 , 65 , 66 ]. Further, gait analysis reveals that gait differs in adults with antero-lateral and posterior exposure during hip arthroplasty compared to healthy ones [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the presence of sarcopenia and obesity within the same individual could potentially accelerate OA disease progression because sarcopenia confers additional risks besides the consequences of excess adiposity. Furthermore, obesity alters gait parameters, including stride length and stance, leading to reduced gait speeds [ 51 ]. Muscle weakness also alters gait kinematics [ 3 ] and the compounded influence of sarcopenia and obesity could impact joint biomechanics.…”
Section: Sarcopenic Obesity and Prevalence Of Knee Oamentioning
confidence: 99%